Secondary buy-outs mechanisms and performances: a quantitative analysis of operating efficiency,profitability and return on investment. - Souliez, Harold G G (2010)
In this paper we provide a description of secondary buy-outs mechanisms, and their evolution in regards to first round buy-outs. While some additional motives are identified, introducing the possibility of performance improvement through the change in ownership structure, we analyse the evolution of some performance indicators. We scanned a 6,633 UK secondary buy-outs database between 2000 and August 2010, as to identify a 108-exited secondary buy-out sample (2000-2009 period). We find conclusive evidence that operating performance, profitability and return on investment changes from first round buy-outs to secondary buy-outs are negative. However secondary buy- outs still out-perform industry peers. Positive influence of private equity backing remains in secondary buy-outs. Nevertheless similar impact of private equity syndication is limited – it only seems to significantly increase resort to leverage. We also identified – in a limited extent – the negative first round buy-outs’ length relationship and the positive secondary buy-outs’ length relationship with secondary buy-outs performance indicator. This suggests that exit through secondary buy-outs only takes place if neither flotation nor trade sale are possible. In addition, the more time allowed for secondary buy-out mechanisms implementation, the greater operating performance and profitability improvements.